FAKTOR-FAKTOR YANG MEMPENGARUHI PRESTASI BELAJAR MAHASISWA PADA MATA KULIAH AKUNTANSI (Studi pada Mahasiswa S1 Akuntansi Universitas Brawijaya) - Yuananto, Yimas Ajeng Larasati (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
The research aims to identify the effect of ability and effort, teaching quality, lecturers’ characteristics, learning habit, and students’ (extra-curricular) activity on the students’ academic achievement in Accounting course. The samples are 95 undergraduate students of Accounting Department batch 2014 at the University of Brawijaya. The hypotheses are tested through multiple linear regression analysis by means of SPSS 20.0 for windows assistance. The result of the study shows that ability and effort, as well as learning habits, give positive effect on the students’ achievement. This is due to the fact that ability, effort, and learning habits are internal factors possessed by the students – they determine the students’ ability to understand the materials given during the lecture. The quality of teaching also positively influences learning achievement. It happens because academic quality determines the learning process and the students’ achievement. In contrast, the lecturers’ characteristics do not influence the students’ learning achievement. This may happen because the student-respondents of this study have a good adjusting ability to all kinds of teaching styles; so that, it does not have any impact on the students’ ability in understanding the materials. Students’ activity also shows no effect on learning achievement because the respondents have allotted specific time to support their learning and organizational activities, i.e. that they do not face any difficulties to balance the academic and organizational programs. Keywords: Students’ academic achievement, Ability, Effort, Teaching quality, Lecturers’ characteristics, Learning habit, Student (extra-curricular) activity.